Pengaruh Profitabilitas, Intensitas Aset Tetap, Ukuran Perusahaan Dan Leverage Terhadap Agresivitas Pajak Di Perusahaan Sektor Perdagangan Besar Yang Terdapat Di Bursa Efek Indonesia Tahun 2017-2022 - Gurusinga, Latersia Br; Handayani, Fitri; Talita, Talita (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In Indonesia, taxes are the main source of revenue to meet the state's needs to finance state household expenditures for the benefit of the general public. Tax revenues from individual taxpayers are a burden that must be paid for taxpayers. Taxes reduce the total income or net profit received by the taxpayer. The aim of this research is to determine the partial and simultaneous impact of profitability, fixed asset intensity, company size and leverage on tax aggressiveness in large trading sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The population used in the research was 49 companies in the Large Trade Sector on the Indonesia Stock Exchange for the 2017-2022 period. The technique used in this research is a purposive sampling technique. It can be seen that the total number of companies that can be used as samples in this research is 21 companies and the research period is 6 years. So the total number of observation data is 126 data. The research results show that profitability, fixed asset intensity, company size and leverage have a partial or simultaneous effect on tax aggressiveness in large trading sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period.